2020
DOI: 10.1002/bjs.11555
|View full text |Cite
|
Sign up to set email alerts
|

Gemcitabine-based adjuvant chemotherapy in subtypes of ampullary adenocarcinoma: international propensity score-matched cohort study

Abstract: Background Whether patients who are resected for ampullary adenocarcinoma have a survival benefit from adjuvant chemotherapy is currently not known. The aim of this study was to compare propensity score-matched survival between patients with and without adjuvant chemotherapy after resection of ampullary adenocarcinoma. Methods An international multicentre cohort study was conducted, including patients who underwent pancreatoduodenectomy for ampullary adenocarcinoma (2006-2017) in 13 centres in six countries. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1
2

Year Published

2021
2021
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 37 publications
1
15
1
2
Order By: Relevance
“…Current evidence for AC in resected ampullary adenocarcinoma is limited to retrospective case series. Recent institutional series by Ecker et al 26 (n = 357 patients; HR: 0.90; CI 95% : 0.51-1.56), Bolm et al 30 with 214 patients (median: 85.0 vs 65.0 months), and Moekotte et al 31 with 1,163 patients (median: not reached vs 32 months) demonstrated no survival benefit with AC. However, these studies are limited by small institutional cohorts and selection bias.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Current evidence for AC in resected ampullary adenocarcinoma is limited to retrospective case series. Recent institutional series by Ecker et al 26 (n = 357 patients; HR: 0.90; CI 95% : 0.51-1.56), Bolm et al 30 with 214 patients (median: 85.0 vs 65.0 months), and Moekotte et al 31 with 1,163 patients (median: not reached vs 32 months) demonstrated no survival benefit with AC. However, these studies are limited by small institutional cohorts and selection bias.…”
Section: Discussionmentioning
confidence: 93%
“…Retrospective single-center, multi-institutional series offer conflicting evidence regarding the benefit of AC. 2,10,[25][26][27][28][29][30][31] Therefore, the use of AC after pancreatoduodenectomy (PD) for ampullary adenocarcinoma remains controversial, especially in patients thought to be at a lower risk for recurrence, such as those with margin-negative resections and node-negative disease.…”
Section: Introductionmentioning
confidence: 99%
“…Cumulative percentages may not exactly equal 100% due to rounding. than distinction based on anatomical site of tumour origin [19]. Further studies on the efficacy of neoadjuvant regimens for periampullary cancers are to be awaited, as is conclusive evidence on the effect of neoadjuvant therapy for (resectable) pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…A consequence of the wider use of gemcitabine-based chemotherapy may be an underestimation of efficacy of adjuvant chemotherapy in the treatment of IIPMNs. However, emerging evidence seemed to suggest that there is a limit to generalisability of results from existing trials to other types of pancreatic cancers owing to differences in tumour biology [ 40 , 41 ]. IIPMNs subtype is a well-established prognostic marker [ 32 , 38 , 42 ].…”
Section: Discussionmentioning
confidence: 99%